A new species of the genus Adapterops (Coleoptera: Anthribidae) from northern Madagascar, with a catalogue and key to species - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2015)
A new species, Adapterops cedrici Trýzna & Baňař sp. nov. (Anthribidae: Choraginae: Araecerini), from northern Madagascar is described and illustrated. A key and catalogue of the genus Adapterops Frieser, 2010 is given.